Psychometric properties of the Lithuanian version of the HEXACO PI-R - Truskauskaitė, I.; Kaniušonytė, G.; Kratavičienė, R.; Kratavičiūtė-Ališauskienė, A. (Psichologija, 2011)
During the last decade, the potential of the dominant five-factor personality model to describe the personality structure was questioned. It has been found that at least six factors are needed for the explication of personality structure (Jackson et al., 1996). Lexical research as well as factor analysis of translated five-factor questionnaires repeatedly revealed that six factors as opposed to five should be used in different languages (Ashton et al., 2004). As a result, the six-factor model providing a better insight into a personality was developed. It consists of the following factors: Honesty–Humility (H), Emotionality (E), Extraversion (X), Agreeableness (A), Conscientiousness (C), and Openness to Experience (O), represented by the acronym HEXACO (Lee and Ashton, 2004). This model, as compared with the five-factor model, has an advantage in psycholexical, theoretical as well as practical terms (Ashton and Lee, 2007). The HECAXO PI-R questionnaire (Ashton and Lee, 2009) is an empirical means of the six-factor model. Different items of the personality questionnaire based on introspection should be accurately translated into the identical meaning in different cultures. Like any other personality structure assessment tool, the HEXACO PI-R questionnaire depends on the language and cultural context, so it is necessary to evaluate the psychometric properties as well as to perform standardisation of the questionnaire in a country in which the questionnaire is applied. The article covers particular psychometric properties of the Lithuanian version of the HE XACO PI-R. 369 students (aged between 19 and 28, including 278 women and 91 men) voluntarily agreed to fill in the HEXACO PI-R questionnaire and participate in this research. The results of the questionnaire have shown that the internal consistency of all the scales that assess personality dimensions is very good while the internal consistency of the subscales that assess subdimensions is sufficient, except for two subdimensions, one of which has a low reliability also in other counties, while the other can be explained by cultural differences. Factor analysis confirmed the relevance of the theoretical model of the six-factor personality model and revealed a very good structural validity of the questionnaire: all subdimensions have the biggest weight in the factors that compose these subdimensions. Also, statistically significant differences were found between men and women in the Honesty–Humility, Emotionality and Conscientiousness scales. The mean scores of women were statistically significantly higher than those of men in all scales. The study showed that the Lithuanian version of HEHEXACO PI-R can be applied in scientific research.
Keywords: personality traits; Six Factor Model; HEXACO PI-R